Analysis of the relationship between primary productivity, phytoplankton abundance and nutrients in Cengklik Reservoir, Boyolali - Pradana, Puspa Rose Rezkyta Winneke; Rahman, Arif; Ain, Churun (Universitas Malikussaleh, 2024)
Cengklik Reservoir is a reservoir that has many benefits for the surrounding community such as irrigation and aquaculture, namely Floating Net Cages. FNC in these waters can have an impact on the remaining feed produced in cultivation. The rest of the feed can cause increased nutrient concentrations and eutrophication in the waters. These impacts can affect water quality conditions, phytoplankton abundance and primary productivity. The purpose of this study was to determine the primary productivity, abundance of phytoplankton, nitrate (NO3) and orthophosphate (PO4) in Cengklik Reservoir, Boyolali. The study was conducted in March 2023. The sampling point determination method uses Stratified Random Sampling with four stations in two repeats. Data processing using simple and multiple linear regression analysis with Jamovi application. The results obtained gross primary productivity value is 62.50 - 156.25 mgC/m3/hour while net primary productivity is 31.25 - 93.75 mgC/m3/hour. The abundance of phytoplankton results the most in the Cyanophyceae class with a percentage of 50.72% - 65.06%. The relationship between phytoplankton abundance and gross primary productivity is obtained R2 = 0.142 while net primary productivity R2 = 0.608 which means that the relationship of phytoplankton abundance affects the production of net primary productivity in waters. The relationship between nitrate and phosphate analysis with phytoplankton abundance in waters R2 = 0.311 which means that nitrate and orthophosphate have a low influence on phytoplankton abundance. The abundance of phytoplankton in waters can be influenced by other factors.Keywords: Cyanophyceae; Nitrate; Orthofosfat; Phytoplankton